Electromigration reliability of interconnections in RF low noise amplifier circuit - He, Feifei (2013)
With the continuous increase of the circuit complexity and the scaling down of the device size, electromigration (EM) failure in the interconnects has become the determining factor for circuit reliability. Most of the EM circuit simulators in the literature are at 2D level. The application of 2D simulators is limited as the actual physical implementation of the circuit in a wafer is indeed 3D in nature, and is much more complicated than 2D. In this paper, we construct a complete 3D circuit model of a RF low noise amplifier (LNA) circuit, including both the intra- and inter-block interconnects. Electric-thermal-structural simulations are performed and the modifications that help to enhance the EM reliability of the circuit are carried out based on the simulation results.